Hidrolisados enzimáticos do concentrado protéico do soro do leite : remoção de fenilalanina, grau de hidrólise e perfil peptídico - Maite Costa da Silva (2009)
One of the purposes of this work was to study the enzymatic conditions for hydrolyzingproteins and the phenylalanine (Phe) removal, using whey protein concentrate (WPC) assubstrate, aiming the preparation a food or a food ingredient to be used in phenilketonuricsdiet. Moreover, WPC hydrolysates were characterized in relation to degree of hydrolysis(DH) and peptide profile, and the effect of the enzyme type, E:S ratio and substrate concentration was analyzed. In addition, the existence of a correlation between the degree of hydrolysis and the peptide profile was verified. Initially, different enzymatic hydrolysisconditions of WPC proteins were studied, and the activated carbon (AC) was used as adsorbent for Phe removal. The effect of some parameters such as enzyme type, E:S ratio, substrate concentration and time of hydrolysis was evaluated. After passing the hydrolysates through an AC column, Phe was quantified by second derivative spectrophotometry (SDS). The use of pancreatin in a E:S of 1:100, substrate concentrationof 10% and reaction time of 5 hours showed to be the most efficient condition, leading to a Phe removal of 81,3%, which corresponds with a final Phe content of 394,1 mg/100g. Then, the degree of hydrolysis of the twelve WPC hydrolysates that showed the highest phenylalanine removal percentage was evaluated by the ratio between á-amino and totalnitrogen. Also, these twelve WPC hydrolysates were analysed in respect to their peptide profile, using the high performance size-exclusion liquid chromatography for the fractionation followed by the Rapid Correct Fraction Area method for quantifying the peptides and free aminoacids. The WPC hydrolysate obtained by the action of pancreatin and A. oryzae protease, both at E:S ratio of 1:100 and substrate concentration of 10%, led to the highest values of degree of hydrolysis (30% and 27% espectively). In respect to peptide profile, the use of the protease from A. oryzae and pancreatin, at E:S ratio of 1:100 and substrate concentration of 10% and 7%, respectively, gave rise to the hydrolysate with the highest di-tripeptide contents (16,14% and 9,12%, respectively) and the lowest level of large peptides (20%, in average). Also, a correlation of low intensity association between the degree of hydrolysis and peptide profile was observed, with positive values for F2, F3 and F4 fractions and negative for F1.